Current-induced domain wall NOT gate logic operation via chirality flipping by exploiting Walker breakdown - Haragopal, Vemuru (2024)
Current-induced domain wall (DW) motion in ferromagnetic nanostructures is an important research area to realize spin-based logic devices. Using micromagnetic simulations, we have designed and demonstrated a NOT gate logic operation via DW chirality flipping in a ferromagnetic nanostructure with an anti-dot. The DW chirality flipping is due to the Walker breakdown occurring at the anti-dot structure. The DW configuration transforms from a transverse DW (TDW) to an anti-vortex DW and back to TDW, however, with opposite chirality when driven by a particular current density. The device is capable of bidirectional operation, wherein the DW driven in both directions undergoes chirality flipping. The DW speed is a critical parameter for the logic operation. The dimensions of the anti-dot govern the DW speed; thus, the successful operation is seen only below the critical anti-dot width. Moreover, the DW needs to travel a certain distance before it can undergo Walker breakdown, making the anti-dot length also a key parameter. Finally, the current density is a pivotal factor in the logic-gate operation. At relatively lower current densities, the DW does not undergo Walker breakdown, whereas it may undergo Walker breakdown with several transformations before it reaches the output at higher current densities. We have shown the window of successful NOT gate logic operation, as a function of anti-dot width, length, and current density.